Cardiovascular Disease Burden in Persons with Mental Illness: Comparison between a U.S. Psychiatry Outpatient Sample and a U.S. General Population Sample - Radha Dhingra; Fan He; Erika F. H. Saunders; Daniel A. Waschbusch; Amanda M. Pearl; Edward O. Bixler; Jody L. Greaney; Alison R. Swigart; Laila Al-Shaar; Vernon M. Chinchilli; Jeff D. Yanosky; Duanping Liao (Mental Illness)
Background. Cardiovascular disease (CVD) and depression are the leading causes of disability in the U.S. Using electronic health record data, we describe the CVD burden among persons with mental illness enrolled in the Penn State Psychiatry Clinical Assessment and Rating Evaluation System (PCARES) Registry between 2015 and 2020. Methods. CVD burden assessment included prevalence of CVD conditions (any major CVD or individual CVD risk factors), indicated medication prescriptions for CVD risk factors, and mean levels of body mass index (BMI, kg/m2), glycosylated hemoglobin (HbA1C, %), glucose (mg/dl), and lipids (mg/dl). We compared the CVD burden between the PCARES sample to a representative sample of adults from the U.S. general population (NHANES 2013-2016) using one-sample chi-square/t-tests for proportions/means. The CVD burden in NHANES participants was adjusted to PCARES age, race, and sex statistics. Results. The PCARES sample (N=3556) had a mean (SE) age of 42.4 (0.3) years and comprised 63.0% women, 85.0% non-Hispanic Caucasians, and 41.0% with major depressive disorder. CVD burden was higher in the PCARES sample compared to NHANES participants for any major CVD (8.6% vs. 4.6%), diabetes (18.4% vs. 10.4%), BMI (30.3 vs. 28.3), HbA1C (6.1 vs. 5.6), cholesterol (185.6 vs. 181.7), triglycerides (153.3 vs. 136.1), and indicated antihypertensive (94.3% vs. 76.9%) and cholesterol-lowering (49.5% vs. 36.7%) medications (Bonferroni-corrected p=0.03 for each outcome). The CVD burden was lower in the PCARES sample compared to NHANES participants for hypertension (45.9% vs. 50.4%), dyslipidemia (43.2% vs. 61.9%), HDL-C (48.4 vs. 41.4), and LDL-C (107.9 vs. 112.0) (Bonferroni-corrected p=0.03 for each outcome). Glucose levels (110.9 vs. 111.9) and indicated antidiabetic medications (87.4% vs. 86.6%) were similar in the two samples (p>0.05). Conclusions. The CVD burden was higher in persons with mental illness compared to the U.S. general population. Integrated mental and physical healthcare services could reduce long-term disability among persons with mental illness.